Examining the Language's Rhetorical Aspects in the Interpretation of Kashf al-Asrar - Maryam Najafi; Mazaher Nikkhah; Asghar Rezaporian (مطالعات زبانی و بلاغی)
The discovery of al-Asrar as a Persian prose book has verbal, lexical, spatial and syntactic features that each one is remarkable in its place. Perhaps the most important of them is the level playing of prose and the great attention paid to Old Persian language – both in the selection of words and in grammar –that makes reading this text more attractive. Considering that the third turn of this interpretation, that is, the mystical interpretation part of language and subject diversity, has a dominant literary and artistic aspect of language. From the point of view of the Religion, as well as from different perspectives of Sufi, you, from the perspective of the wise, the love-loving, and the sectarian, spoke of your subjects. And in the expression of each of the views, the language also has different characteristics; the linguistic analysis of the linguistic features of this valuable comment - especially in the third turn - seems essential. Therefore, the present study demonstrates the following hypothesis in order to reveal the rhetorical and linguistic values of Meybod's interpretation: The beauty of the third part of the collection, in addition to the variety of archetypes and techniques associated with the music of the word, is due to literary tricks from the rhetorical aspects of language. The research method in this research is descriptive and analyzes the content about the style (language) of the third turn of Kashf al-Asrar.